ChemInform Abstract: A New Recoverable Au(III) Catalyst Supported on Magnetic Polymer Nanocomposite for Aromatic Bromination. Issue 23 (16th May 2013) - Li, Bai; Gao, Linfeng; Bian, Fengling; Yu, Wei
Abstract The catalyst (I) can be used for the halogenation process with an activity that is comparable to homogeneous AuCl3.